O zumbi de Bruce LaBruce em Otto; or, Up with dead people - Silva, Thales Figueiredo da (2017)
The Canadian filmmaker Bruce LaBruce has a production focused on the discussions of the LGBT + theme, with questions about sexual gender and cinematographic language. In Otto; or, Up with dead people (2008) he uses for the first time the zombie like element to elaborate the subjects that are expensive to his work. From the study of this film we intend to explore the strategies employed by this queer filmmaker, so we can point out some possible reasons that led him to work with a character with a great tradition of cinema as the zombie.